- Thread starter
- #1

- Thread starter shamieh
- Start date

- Thread starter
- #1

- Admin
- #2

- Mar 5, 2012

- 9,806

Your notation is a bit confusing to me. So let me write it as I'm used to.Find the simplified equation (SOP FORM) corresponding to the following circuit (i.e. apply Demorgan's theorem to bring the negations inside the parenthesis).

View attachment 1466

So is it saying W NAND X which means (w!x!) + YNORZ so (w!x!) + (y!z!) = wxyz?

You have f = (w NAND x) NOR (y NOR z).

Written in boolean form this is:

$$f = \overline{\overline{wx} + \overline{y+z}}$$

Applying De Morgan's Theorem ($\overline{p+q} = \overline p \cdot \overline q$) yields:

$$f = \overline{\overline{wx}} \cdot \overline{\overline{y+z}} = wx(y+z)$$

Perhaps you can simplify it further to SoP form?